Realization of Temporal Valance by Verbs of Semantic Field “Agricultural Production (Crop Production)” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The analysis of temporal valence of verbs of semantic field “agricultural production (crop production)”, which is realized in semantic positions “to begin to perform an action”, “to perform an action for some time”, “to finish performing an action”, is done in the article. The reasons which affect the manifestation of temporal modifications within the analyzed semantic field are also explained.
Keywords: temporal valence; derivative; semantic field; temporal modifications